155 COMPLICATIONS OF SIMULTANEOUS TREATMENT OF TUBERCULOSIS AND HIV IN AN HIV-POSITIVE MAN. (10th December 2015) - Wang, S. H.; Menon, A.; Hyslop, N. E.
Abstract : Introduction: In HIV-tuberculosis (TB) coinfection, treatment (Rx) principles for TB are identical to HIV-uninfected individuals. However, Rx problems may be encountered, including drug interactions and paradoxical immune reactions, as illustrated by a HIV-TB coinfected individual with extrapulmonary complications of TB. Case Report: A previously healthy 17 year old Hispanic male presented to Medical Center of Louisiana, New Orleans(MCLNO), with 8 week history of cough, pleurisy, dyspnea on exertion, fever, night sweats, chills, and 10 pound weight loss. Pertinent findings on admission were T 39.4°, BP 110/60, P 108, RR 26 with unremarkable physical examination and laboratory results. CXR revealed hilar fullness but no infiltrate. Chest CT scan revealed superior and mediastinal lymphadenopathy. Sputum acid-fast bacilli (AFB) smears and TB skin test were negative. HIV test was positive with a CD4 count of 41/mm 3 and viral load (VL) of 199, 000 copies. The patient was empirically treated with levofloxacin (levo) with improvement and discharged. Two weeks after initial hospitalization, the patient was readmitted with worsening symptoms, and isoniazid, rifampin (RIF), pyrazinamide, and ethambutol were started empirically with improvement. On day 20, initial sputum culture turned positive for Mycobacterium TB. Highly active antiretroviral therapy (HAART) was started as an outpatient with D4T, 3TC, and abacavir. On day 60, the patient presented to an outside hospital with return of fever, chills, and pleurisy. Echocardiogram revealed large pericardial effusion with tamponade. Thoracoscopic pericardial window and biopsy was performed with removal of 700 cc of serosanguinous fluid but minimal relief of symptoms. Levo was substituted for RIF, and HAART was changed to D4T, DDI, and lopinavir/ritonavir. The patient continued to worsen and on day 81 was transferred back to MCLNO. HAART and levo were discontinued and RIF reinstituted. Indomethacin failed but prednisone gave complete resolution of symptoms and pericardial fluid by day 88. HAART was restarted with D4T, 3TC, and efavirenz, with subsequent VL suppression and CD4 peak of 294/mm 3 . The patient completed 10 months of anti-TB therapy with no recurrence for >3 years. Discussion: Due to high mortality in HIV infected persons with TB, early treatment with HAART is recommended, but time of initiation is controversial. Providers must be alert to complications such as drug interactions and immune reconstitution syndrome that may mimic worsening of TB.